Efficient Promotion of Autophagy and Angiogenesis Using Mesenchymal Stem Cell Therapy Enhanced by the Low-Energy Shock Waves in the Treatment of Erectile Dysfunction. (29th August 2018) - Zhu, Guan Qun; Jeon, Seung Hwan; Bae, Woong Jin; Choi, Sae Woong; Jeong, Hyun Cheol; Kim, Kang Sup; Kim, Su Jin; Cho, Hyuk Jin; Ha, U. Syn; Hong, Sung Hoo; Lee, Ji Youl; Kwon, Eun Bi; et al.
Abstract : Background . Mesenchymal stem cell therapy (MSCT) and defocused low-energy shock wave therapy (ESWT) has been shown to ameliorate erectile dysfunction (ED). However, the interactions and effects of action between MSCT and ESWT remain poorly understood. In this study, we investigated the mechanisms of combination therapy with MSCT and ESWT in a rat model of diabetic ED. Materials and Methods . Eight-week-old male Sprague-Dawley rats were randomly divided into 2 parts. Diabetic rats induced by streptozotocin (65 mg/kg) were randomly divided into 4 groups: (1) DM control group, (2) DM + ESWT group, (3) DM + MSCT group, and (4) DM + ESWT + MSCT group. The sham group was a normal control group (without streptozotocin). MSCT and (or) ESWT were, respectively, administered to each group according to the proposal for 8 weeks. Immediately after recording of intracavernous pressure (ICP), the penis was then harvested for histologic analysis, ELISA, and Western blotting. Results . The ratio of ICP/MAP was significantly higher in the DM + ESWT + MSCT group than in ESWT or MSCT treated group (P < 0.05 ). Also, the treatment stimulated angiogenesis and vasodilatation in the corpus cavernosum (P < 0.05 ). ESWT increased the quantity of MSCs in the corpus cavernosum and also induced MSCs to express more VEGF in vitro and vivo (P < 0.05 ) which activated the PI3K/AKT/mTOR and NO/cGMP signaling pathways in the corpus cavernosum. The combination approach stimulated autophagy and decreased apoptosis in the corpus cavernosum. NGF and BDNF expressions were higher in the DM + ESWT + MSCT group than in the DM control group (P < 0.01 ). Furthermore, the treatment promoted the MSC recruitment by inducing penile tissues to express more PECAM and SDF-1. Conclusions . Combination of LI-ESWT and MSCT can get a better result than a single treatment by expressing more VEGF which can take part in autophagy by triggering the PI3K/AKT/mTOR signaling pathway. This cooperative therapy would provide a new research direction in ED treatment for the future.